Beyond Self-Control: Mechanisms of Hedonic Goal Pursuit and Its Relevance for Well-Being. (April 2021) - Bernecker, Katharina; Becker, Daniela
Self-control helps to align behavior with long-term goals (e.g., exercising to stay fit) and shield it from conflicting hedonic goals (e.g., relaxing). Decades of research have shown that self-control is associated with numerous positive outcomes, such as well-being. In the present article, we argue that hedonic goal pursuit is equally important for well-being, and that conflicting long-term goals can undermine it in the form of intrusive thoughts. In Study 1, we developed a measure of trait hedonic capacity, which captures people's success in hedonic goal pursuit and the occurrence of intrusive thoughts. In Studies 2A and 2B, people's trait hedonic capacity relates positively to well-being. Study 3 confirms intrusive thoughts as major impeding mechanism of hedonic success. Studies 4 and 5 demonstrate that trait hedonic capacity predicts successful hedonic goal pursuit in everyday life. We conclude that hedonic goal pursuit represents a largely neglected but adaptive aspect of self-regulation.